2016
DOI: 10.1136/rmdopen-2015-000171
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors predict adherence to methotrexate in rheumatoid arthritis; findings from a systematic review of rates, predictors and associations with patient-reported and clinical outcomes

Abstract: Treatment response to methotrexate (MTX) for rheumatoid arthritis (RA) is not universal and non-adherence may partially explain this. The aims of this systematic review were to: (1) summarise existing rates of adherence to MTX, (2) identify predictors of adherence to MTX, and (3) assess the association between non-adherence and patient outcomes. The authors conducted a systematic search of papers published from January 1980 to February 2015 in PubMed, PsycINFO, EMBASE and CINAHL databases. Studies were eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
(118 reference statements)
0
47
0
Order By: Relevance
“…Its treatment is now well codified; MTX is the first‐line drug and is usually maintained when biologics become necessary . Various studies suggest that adherence may be suboptimal in 25% of patients taking MTX . In the current study, the proportion of nonadherent patients was slightly higher (close to 40%), since the use of a combination of scores is known to avoid the overestimation of adherence .…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Its treatment is now well codified; MTX is the first‐line drug and is usually maintained when biologics become necessary . Various studies suggest that adherence may be suboptimal in 25% of patients taking MTX . In the current study, the proportion of nonadherent patients was slightly higher (close to 40%), since the use of a combination of scores is known to avoid the overestimation of adherence .…”
Section: Discussionmentioning
confidence: 55%
“…In RA, the estimated percentage of patients with good adherence to MTX ranges from 59% to 100%, depending on the evaluation method used . In a pooled analysis of 13,358 patients in published MTX adherence studies, this percentage was 75.6% . Studies based on electronic medication event monitoring systems gave similar results .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonadherence to DMARD has been associated with symptom worsening and increased disability 9,10 , and high adherence has been linked to lower disease activity 11,12 . A previous narrative review found no clear pattern in factors that influence medication adherence in patients with RA 5 , whereas a systematic review of methotrexate (MTX) use in RA suggested improved adherence was associated with belief in the necessity and efficacy of MTX, absence of low mood, mildness of disease, and monotherapy with MTX 13 .…”
mentioning
confidence: 99%
“…Although several systematic or comprehensive reviews have evaluated adherence to DMARD in general 7,17,18 , only 1 systematic study, to our knowledge, has specifically evaluated MTX adherence (but not persistence) in patients with RA 13 . Given the prevalence of MTX use and its involvement in combination treatment with biologics, it is important to understand factors that may cause patients to be nonadherent or to discontinue treatment.…”
mentioning
confidence: 99%